Early pregnancy loss in the emergency department, 2006–2016. Issue 6 (5th November 2021) - Benson, Lyndsey S.; Magnusson, Sara L.; Gray, Kristen E.; Quinley, Kelly; Kessler, Larry; Callegari, Lisa S.
Abstract: Objectives: Women experiencing early pregnancy loss (EPL) frequently present to the emergency department (ED), but little is known about who receives EPL care in these settings. We aimed to estimate the proportion of ED visits for EPL‐related care and determine characteristics associated with seeking care for EPL in the ED in a national sample. Methods: We conducted a secondary analysis of the 2006–2016 National Hospital Ambulatory Medical Care Survey (NHAMCS), a nationally representative survey of US ED visits. We identified women ages 15–44 years who presented to the ED for threatened or confirmed EPL based on diagnosis code or chief complaint. We estimated the proportion of ED visits attributable to EPL‐related care among all ED visits and among women 15–44 years old. Using multivariable logistic regression, we evaluated patient and visit characteristics associated with receiving EPL‐related care versus all other care. Results: The 2006–2016 NHAMCS dataset included 325, 037 visits (weighted n = 1, 447, 144, 423), including 82, 871 visits among women ages 15–44 years (weighted n = 371, 016, 125). Of all ED visits for women ages 15–44 years, 2.7% (95% confidence interval, 2.5–2.9) were for EPL‐related care. This equates to ≈900, 000 visits annually. Compared with women ages 15–44 years presenting to the ED for other reasons, those presenting for EPL‐related care were younger and more likely to be Black or Hispanic. Conclusions: EPL‐related care accounts for over 900, 000 ED visits in the United States each year. These findings highlight the current burden of EPL visits upon EDs nationally.